2012
DOI: 10.4236/ojab.2012.13004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preparation and Storage of Agar Media on the Sensitivity of Bacterial Forward Scattering Patterns

Abstract: Recent worldwide foodborne outbreaks emphasize the need for the development of rapid and accurate method for pathogen detection. To address such issues, a new colony based label-free detection method working on the principles of elastic light scattering was introduced. In order to build libraries of scattering images for bacterial pathogens, it is pertinent to determine the effect of preparation and storage of the agar media on the scatter patterns. Scatter patterns of three Escherichia coli serovars (O26, O11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As the modeling of forward scattering pattern for the bacteria colony shows, the morphology and optical characteristics play major roles into formation of diffraction patterns. Previous studies have shown that availability of nutrients and agar concentration (Bae et al, 2011 ), and storage condition of the agar plate (Mialon et al, 2012 ) possibly affect the distribution/propagation of cells within a colony and the resulting diffraction pattern. Furthermore, previous studies (Bae et al, 2007 , 2010 ; Kim et al, 2013 ) indicate that the forward scattering patterns produced by BARDOT are circular symmetric or concentric circle with some radial spokes for most of the microorganisms ( E. coli , Listeria , Salmonella , and Staphylococcus ) studied.…”
Section: Discussionmentioning
confidence: 99%
“…As the modeling of forward scattering pattern for the bacteria colony shows, the morphology and optical characteristics play major roles into formation of diffraction patterns. Previous studies have shown that availability of nutrients and agar concentration (Bae et al, 2011 ), and storage condition of the agar plate (Mialon et al, 2012 ) possibly affect the distribution/propagation of cells within a colony and the resulting diffraction pattern. Furthermore, previous studies (Bae et al, 2007 , 2010 ; Kim et al, 2013 ) indicate that the forward scattering patterns produced by BARDOT are circular symmetric or concentric circle with some radial spokes for most of the microorganisms ( E. coli , Listeria , Salmonella , and Staphylococcus ) studied.…”
Section: Discussionmentioning
confidence: 99%
“…The media included: BHI agar, Sorbitol MacConkey (SMAC; Becton Dickinson) agar, Rainbow Agar O157 (Biolog, Hayward, CA), BBL CHROMagar O157 (Becton Dickinson), and R&F E. coli O157:H7 medium (R&F Products, Downers Grove, IL). Agar plates were prepared as instructed by the manufacturer, tempered to 45°C, dispensed 20 mL/plate, cooled at room temperature for 10–20 min, and stored in a sealed plastic bag until use (used within 7–30 days) [54] . After plating appropriate dilutions of bacterial cultures, the plates were incubated at 37°C for 10–12 h or until the colony size reached 1.1±0.1 mm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…As the modeling of forward scattering pattern for the bacteria colony shows, the morphology and optical characteristics play major roles into formation of diffraction patterns. Previous studies have shown that availability of nutrients and agar concentration (Bae et al, 2011), and storage condition of the agar plate (Mialon et al, 2012) possibly affect the distribution/propagation of cells within a colony and the resulting diffraction pattern. Furthermore, previous studies (Bae et al, 2007Kim et al, 2013) indicate that the forward scattering patterns produced by BARDOT are circular symmetric or concentric circle with some radial spokes for most of the microorganisms (E. coli, Listeria, Salmonella, and Staphylococcus) studied.…”
Section: Discussionmentioning
confidence: 99%